Penerapan Argument Driven Inquiry Berbasis SSI Untuk Meningkatkan Keterampilan Argumentasi Ilmiah Pada Materi Perubahan Lingkungan - Isnaeni Sulton Fathonah; Joko Ariyanto; Umi Fatmawati (Universitas Sebelas Maret, 2025)
The independent curriculum emphasizes 21st-century skills, including the 4Cs (critical thinking, communication, collaboration, and creativity). An important aspect of achieving the skills in the independent curriculum is the ability to present arguments. This study aims to (1) determine the implementation of the Argument-Driven Inquiry model based on SSI and (2) assess the improvement in scientific argumentation skills of Grade 10 students at State High School 7 Surakarta through the application of the Argument-Driven Inquiry model based on SSI. This study is a two-cycle Classroom Action Research. The population used was students in Class X-C of SMA Negeri 7 Surakarta in the 2024/2025 academic year. The research data consisted of written scientific argumentation skills measured based on test results. Data collection techniques included tests, observations, interviews, and documentation. Data validity was tested using the triangulation method. Data analysis techniques used qualitative descriptive methods. The achievement indicator was an overall increase in scientific argumentation skills to 75%. The research procedure included planning, implementation, observation, and reflection. The results showed that the implementation of Argument Driven Inquiry based on SSI could improve students' scientific argumentation skills. The average scientific argumentation skills of students in the pre-intervention phase were 49%, in Cycle I 64,3%, and in Cycle II 75.9%. It is hoped that this research can be used as a reference for the application of Argument Driven Inquiry based on SSI for similar research and as a consideration for teachers to achieve optimal learning.